Knowledge and willingness of physicians about deprescribing among older patients: a qualitative study - Alrasheed MM (Dove Medical Press, 2018)
Maha M AlRasheed,1 Tariq M Alhawassi,1–3 Alanoud Alanazi,1 Nouf Aloudah,1 Fowad Khurshid,1 Mohammed Alsultan1 1Department of Clinical Pharmacy, College of Pharmacy, King Saud University, Riyadh, Saudi Arabia; 2Medication Safety Research Chair, College of Pharmacy, King Saud University, Riyadh, Saudi Arabia; 3Pharmacy Services, King Saud University Medical City, Riyadh, Saudi Arabia Purpose: This study aimed to explore the physician’s knowledge and identify the perceived barriers that prevent family medicine physicians from engaging in deprescribing among older patients. Methods: This qualitative study was designed and conducted using an interpretive theoretical approach. Purposive sampling was undertaken, whereby family medicine physicians of King Saud University Medical City (KSUMC), Riyadh, Saudi Arabia, were invited to participate in the study. The topic guidelines were designed to give the physicians the freedom to express their views on exploring their knowledge about deprescribing and to identify the perceived barriers and enablers that prevent them from engaging in the practice in older patients. The focus group discussions were conducted in English, audio-taped with permission, and transcribed verbatim. Each transcript was independently reviewed and coded separately to explore the themes and sub-themes. Results: A total of 15 physicians participated in three focus group discussions. Their thematic content analysis identified 24 factors that facilitated or hindered deprescribing. The facilitators included cost-effectiveness and time effectiveness, side effects avoidance, clinical pharmacist’s role, need for system(s) to help in applying deprescribing, and patient counseling/education. Similarly, barriers included lack of knowing the deprescribing term and process, patient comorbidities, risk/fear of conflict between physicians and clinical pharmacists, lack of documentation and communication, lack of time or crowded clinics, and patient resistance/acceptance. Conclusion: The study identified several factors affecting family medicine physician’s deprescribing behavior. The use of theoretical underpinning design helped to provide a comprehensive range of factors that can be directed when defining targets for intervention(s). Keywords: deprescribing, barrier, enablers, polypharmacy